2017
DOI: 10.1016/j.oregeorev.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Geological, geochemical and mineralogical characteristics of REE-bearing Las Mercedes bauxite deposit, Dominican Republic

Abstract: Bauxite deposits, traditionally the main source of aluminum, have been recently targeted for their remarkable contents in rare earth elements (REE). With ƩREE (lanthanoids + Sc + Y) concentrations systematically higher than ~ 1400 ppm (av. = 1530 ppm), the Las Mercedes karstic bauxites in the Dominican Republic rank as one of the REE-richest deposits of its style.The bauxitic ore in the Las Mercedes deposit is mostly unlithified and has a homogeneous-massive lithostructure, with only local cross-stratification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 48 publications
1
25
0
1
Order By: Relevance
“…On the other hand, weathering has been proven an efficient process for concentrating certain CE. The present study illustrates this point, and economic concentrations of CE have been found in other weathering profiles, soils and laterites worldwide [8,10,11,[74][75][76][77]. In fact, it is well known that the mineral structures of aluminophosphates of the alunite supergroup, such as florencite or goyazite, can concentrate REE at economic grades in lateritised carbonatites and karstic bauxites [74,78,79].…”
Section: Weathered Phosphates As Non-conventional Source Of Critical supporting
confidence: 78%
“…On the other hand, weathering has been proven an efficient process for concentrating certain CE. The present study illustrates this point, and economic concentrations of CE have been found in other weathering profiles, soils and laterites worldwide [8,10,11,[74][75][76][77]. In fact, it is well known that the mineral structures of aluminophosphates of the alunite supergroup, such as florencite or goyazite, can concentrate REE at economic grades in lateritised carbonatites and karstic bauxites [74,78,79].…”
Section: Weathered Phosphates As Non-conventional Source Of Critical supporting
confidence: 78%
“…3. Also, many bauxite ore deposits in the World are different from Grebnik's primarily due to their major gibbsite composition, with or without diaspore and boehmite constituents as major or minor (BÁRDOSSY, 1982;ZARASVANDI et al, 2008;MESHRAM & RANDIVE, 2011;JADHAVI et al, 2012;YUSTE et al, 2015;TORRÓ et al, 2017).…”
Section: Comparison With Some Other Bauxite Ore Depositsmentioning
confidence: 99%
“…However, REE fractionations and redistributions have been reported from various bauxite deposits due to evolution of geochemical systems in various mechanisms and conditions such as mobilization of REE, supergene processes, surficial weathering, diagenetic processes, presence of REEbearing mineral phases, pH of solutions and/or depositional environment, and existence of organic and/or non-organic complexing ligands (Mondillo et al, 2011;Abedini and Calagari, 2013;Mongelli et al, 2014Mongelli et al, , 2016Mongelli et al, , 2017Liu et al, 2016;Buccione et al, 2016;Hou et al, 2017;Khosravi et al, 2017;Long et al, 2017;Radusinovic et al, 2017;Torró et al, 2017;Yuste et al, 2017;Chen et al, 2018). Generally, these Fig.…”
Section: Introductionmentioning
confidence: 99%